Multi-Objective Optimization Framework for Timber-Based Geriatric Facilities: Integrating Material Performance and Spatial Adaptability - Tiexin Dong; Chang Chen; Yuanhe Li; Dongnan Han; Xuming Wang; Yu Duan (BioResources, 2025)
An integrated design framework was developed to optimize timber-based elderly care facilities across three critical dimensions: environmental performance, health outcomes, and economic feasibility. By systematically analyzing engineered timber’s thermal regulation, humidity control, and biophilic properties, a data-driven model was established that balances material science with spatial adaptability requirements. It was found that cross-laminated timber (CLT) walls reduce HVAC energy consumption by 17% through delayed heat transmission, while maintaining stable indoor humidity levels (40 to 60% RH), which is crucial for respiratory health. The framework achieved a 23% improvement in elderly satisfaction compared to conventional designs, which can be attributed to wood’s natural terpene emissions and optimized spatial configurations. Modular timber partitions enabled rapid layout reconfiguration (2-hour adjustments) while maintaining acoustic insulation and wheelchair accessibility standards. Lifecycle analysis revealed 14% higher cost-effectiveness through prefabrication advantages and material durability. A case study validation showed timber systems support 12% larger window areas without compromising thermal performance, confirming practical applicability. This research provides a replicable model for integrating sustainable materials with geriatric care architecture, addressing both climate challenges and aging population needs.